INTEGRASI SPIRITUAL-RASIONAL: SINTESIS STRUKTUR DAN HIERARKI ILMU MENURUT IMAM AL-GHAZALI DAN IMAM AL-FARABI - Handayani, Afni (Sulesana: Jurnal Wawasan Keislaman, 2025)
This study explores the structure and hierarchy of knowledge in the thoughts of Imam Al-Ghazali and Imam Al-Farabi, as well as their relevance in constructing a contemporary paradigm of science. Both scholars represent two major poles in the Islamic intellectual tradition: philosophical rationality and ethical spirituality. Al-Farabi emphasizes the importance of logical and systematic reasoning as the foundation for scientific development, while Al-Ghazali highlights the moral and spiritual dimensions that guide knowledge toward its ultimate purpose—true happiness and closeness to God. Using a library research method with a comparative-philosophical approach, this study reveals that the synthesis between rationality and spirituality generates an evolution called Spiritual-Rational Integration, which positions reason as the means to discover scientific truth and revelation as the ethical compass for its application. In the digital era, this paradigm serves as a solution to the moral disorientation of modern science and offers a balanced path between technological progress, humanity, and divinity.